EFFECT OF UPRIGHT POSITION ON FIRST STAGE PAIN IN PRIMIPAROUS MOTHER'S ACTIVE PHASE OF LABOR AT THE PUSKESMAS JUMPANDANG BARU MAKASSAR 2019 - Dewi Parwati; Susanti Susanti (Lembaga Pengembangan Kinerja Dosen, 2022)
The first stage process accompanied by pain which is a physiological process, is a subjective experience of physical sensations associated with uterine contractions, dilation and cervical thinning. Primiparous mothers are often worried because they do not understand how to deal with labor. Primipara tends to experience more anxiety to cause tension and fear so that it cannot withstand the pain. The purpose of this study was to look for the effect of an upright position on pain in the first phase of the active phase of primiparous labor in the Puskesmas Jumpandang Baru Makassar in 2019. The study was conducted in January to October 2019 at the Jumpandang Baru Public Health Center in Makassar. This type of research is a quantitative experiment with the Post Test Only Group Design approach. The population in this study were all women giving birth at the Jumpandang Baru Makassar health center in January to October 2019. The sample in this study was part of the population of women giving birth at the Jumpandang Baru Makassar health center in January to October 2019 as many as 15 people with Purposive Sampling.